A study on effect of 4% total solid for biogas production from wastewater in anaerobic digestion at Indah Water Konsortium (IWK) treatment plant - Nik Nurul Ilani , N Redzauddin (2012)
Nowadays, the population in Malaysia is increased and as a result, the production of waste also increased. Through the industry awareness and the experimental effort, this sewage water has a huge potential to produce byproduct and it is biogas. Biogas is used to generate heat and electricity and as a result, it can save energy and save the environment. In this study, anaerobic digestion process was involved in the production of biogas. This process can occur with some appropriate conditions. This study is involves the comparison between pH 5 and pH 7 conditions. Besides that, this study is also involves the comparison between 5m1 and 1 5m1 inoculums recirculation and it is to make sure the most suitable conditions between both recirculation that can produce higher biogas in anaerobic digestion process. Based from the results of this study, the production of biogas in pH 7 is higher than pH 5, while in 15 ml of inoculums recirculation, the production of biogas is higher than in the 5m1 inoculums recirculation. So, as a conclusion, the anaerobic digestion process can occur well and can increase the production of biogas at pH 7 and 15 ml inoculums recirculation.